2001
DOI: 10.7326/0003-4819-134-5-200103060-00008
|View full text |Cite
|
Sign up to set email alerts
|

Therapy for Helicobacter pylori in Patients with Nonulcer Dyspepsia

Abstract: This meta-analysis provides little support for the use of H. pylori eradication therapy in patients with nonulcer dyspepsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
148
1
6

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(156 citation statements)
references
References 20 publications
1
148
1
6
Order By: Relevance
“…Many studies have shown good symptomatic response after anti-H. pylori treatment in patients with functional dyspepsia 12-14 whereas others have not observed a positive effect of anti-H. pylori treatment on symptoms of functional dyspepsia. [15][16][17] The results of the present study are in favour of an aetiological role of H. pylori in patients with functional dyspepsia. H. pylori was found in 65% of the patients with functional dyspepsia.…”
Section: Discussionmentioning
confidence: 50%
“…Many studies have shown good symptomatic response after anti-H. pylori treatment in patients with functional dyspepsia 12-14 whereas others have not observed a positive effect of anti-H. pylori treatment on symptoms of functional dyspepsia. [15][16][17] The results of the present study are in favour of an aetiological role of H. pylori in patients with functional dyspepsia. H. pylori was found in 65% of the patients with functional dyspepsia.…”
Section: Discussionmentioning
confidence: 50%
“…While eradication of Helicobacter pylori has been advocated for the treatment of patients with functional dyspepsia, the results of such eradication studies have been generally disappointing and any long-term benefit is debatable. 10 Finding convincingly effective treatment options thus continues to be an important goal.…”
Section: Introductionmentioning
confidence: 99%
“…severe inflammation and more significant gastroduodenal pathologies but not with symptom severity or clinical outcome (2,3,6,8).…”
Section: Discussionmentioning
confidence: 99%
“…The role of H. pylori testing and treatment in patient management is a major component of all of these guidelines, although recently published data do not support the view that treatment of H. pylori has a beneficial effect on symptoms and quality of life (2). However, some studies have revealed the beneficial effect of treatment for H. pylori eradication in some dyspepsia subgroups (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation